Tunable Filters Based on Cascaded Long-Period Polymer Waveguide Gratings - Xin Shi; Rui Cao; Lingfang Wang (Photonic Sensors, 2022)
Abstract Long-period waveguide grating based filters have attracted attention due to their flexible fabrication, a variety of materials and structures, low back reflection, low insertion loss, and excellent performance in the tuning range and temperature sensitivity. To our knowledge, for the first time, a two-segment polymer long-period waveguide grating was cascaded to implement a filter with a narrower bandwidth. Experimental results showed that the device had a maximum extinction ratio of 24 dB at 1 577 nm, and the 12 dB bandwidth was 10 nm. The temperature sensitivity of the fabricated device was 1.79 nm/°C.